Impact of Sharia Mutual Funds and Sharia Stocks on The Economic Growth of Indonesia In The Period of 2013-2022 - Aulia, Kharisma; Suhirman, Gatot; Susianti , Nurul (UIN Mataram, 2024)
The research aimed at determining whether Sharia mutual funds and Sharia stocks have an influence on the economic growth of Indonesia as measured by the growth of Indonesia's Gross Domestic Product (GDP). This type of research is quantitative research with an associative approach. The data collection technique is by taking data from the official website of the National Central Statistics Agency, the Indonesian Stock Exchange and the Financial Services Authority. This research also uses other secondary sources such as scientific journals and theses which are appropriate to this research. The study employs prerequisite tests with classic assumption tests, followed by hypothesis testing using multiple linear regression with the analytical tool EViews-12. From the test results, a multiple linear equation model was obtained: Y = 1.319125 + 0.022249*X1 + 0.001161*X2. The Sharia mutual funds variable (X1) is significant to Indonesian economic growth (Y) with a probability value of 0.0190 < 0.05, indicating that Sharia mutual funds significantly influence Indonesian economic growth. The Sharia stocks variable (X2) is significant to Indonesian economic growth (Y) with a probability value of 0.0200 < 0.05, showing that Sharia stocks significantly affect Indonesian economic growth. Simultaneously, they significantly affect the dependent variable, meaning that Sharia mutual funds and Sharia stocks collectively have a significant impact on Indonesian economic growth. Looking at the regression, the R-Squared value is 0.889354, which means that the influence of the independent variables on the dependent variable is 88%, while 12% is influenced by other variables.